2016
DOI: 10.1001/jamaneurol.2016.3751
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Incremental Diagnostic Value of Florbetapir F 18 Imaging in Patients With Cognitive Impairment

Abstract: ; for the Incremental Diagnostic Value of Amyloid PET With [ 18 F]-Florbetapir (INDIA-FBP) Working Group IMPORTANCE Cerebral amyloidosis is a key abnormality in Alzheimer disease (AD) and can be detected in vivo with positron emission tomography (PET) ligands. Although amyloid PET has clearly demonstrated analytical validity, its clinical utility is debated. OBJECTIVE To evaluate the incremental diagnostic value of amyloid PET with florbetapir F 18 in addition to the routine clinical diagnostic assessment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 44 publications
2
73
1
Order By: Relevance
“…Sixteen studies concerning the clinical utility of amyloid PET imaging were found in the literature (17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Supplemental Table 3 summarizes these studies.…”
Section: Clinical Utility Of Amyloid Imagingmentioning
confidence: 99%
“…Sixteen studies concerning the clinical utility of amyloid PET imaging were found in the literature (17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Supplemental Table 3 summarizes these studies.…”
Section: Clinical Utility Of Amyloid Imagingmentioning
confidence: 99%
“…Five studies were conducted in the US [7, 14, 15], 2 studies in the UK [16, 17], 2 in Netherlands [18, 19], and 1 each in Italy [10], Canada [20], France [21], and Denmark [22]. Two studies were multicenter studies with one study conducted in Australia, Germany, Japan, Switzerland, and USA [23], and the other in France, Italy, and USA [24].…”
Section: Resultsmentioning
confidence: 99%
“…In cases where prescan diagnosis was AD, the rate of change in diagnosis ranged from 13 to 37% [10, 15, 18-20, 25, 26]. When prescan diagnosis was non-AD etiology, diagnostic change ranged from 14 to 62% [10, 18-20, 26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative amyloid scan indicates sparse to no amyloid plaques and is inconsistent with a diagnosis of AD (5). A negative amyloid scan in a patient who has a clinical diagnosis of AD has been shown to be of great clinical value, as it suggests a misdiagnosis and often results in changes to subsequent therapeutic planning (6).…”
Section: Discussionmentioning
confidence: 99%